Striking the Right Balance: The Role of n-3/n-6 Fatty Acid Ratio in Health and Strategies for Dietary Improvement. - Poonam Bakhetia (International Journal of Nutritions, 2026)
The dietary balance between omega-3 (n-3) and omega-6 (n-6) polyunsaturated fatty acids (PUFAs) is crucial in modulating inflammation and promoting optimal physiological function. Modern diets, particularly in industrialized countries, are skewed heavily in favor of n-6 fatty acids, often reaching ratios as high as 1:20 or more, compared to the ideal range of 1:1 to 1:4. This imbalance is associated with the pathogenesis of numerous chronic diseases, including cardiovascular conditions, obesity, diabetes, neurodegenerative disorders, and certain cancers. This review integrates evidence from approximately 45 original research studies to discuss the biological relevance of the n-3/n-6 ratio, its implications for health, and feasible dietary strategies for restoring balance. It also explores historical and cultural dietary patterns, biochemical pathways, and emerging public health interventions. The restoration of a healthy n-3/n-6 ratio is not only a nutritional priority but a public health imperative.This review integrates evidence from approximately 45 original research studies to discuss the biological relevance of the n-3/n-6 ratio, its implications for health, and feasible dietary strategies for restoring balance. It also explores historical and cultural dietary patterns, biochemical pathways, and emerging public health interventions. The restoration of a healthy n-3/n-6 ratio is not only a nutritional priority but a public health imperative.
Keywords: Keywords: Omega-3 fatty acids (n-3 PUFAs); inflammation modulation; n-3/n-6 ratio; omega-6 fatty acids (n-6 PUFAs); polyunsaturated fatty acids